Methanogenic Community Was Stable in Two Contrasting Freshwater Marshes Exposed to Elevated Atmospheric CO2 - Lin, Yongxin; Liu, Deyan; Yuan, Junji; Ye, Guiping; Ding, Weixin (Frontiers in Microbiology, 2017)
The effects of elevated atmospheric CO2 concentration on soil microbial communities have been previously recorded. However, limited information is available regarding the response of methanogenic communities to elevated CO2 in freshwater marshes. Using high-throughput sequencing and real-time quantitative PCR, we compared the abundance and community structure of methanogens in different compartments (bulk soil, rhizosphere soil and roots) of Calamagrostis angustifolia and Carex lasiocarpa growing marshes under ambient (380 ppm) and elevated CO2 (700 ppm) atmospheres. C. lasiocarpa rhizosphere was a hotspot for potential methane production, based on the 10-fold higher abundance of the mcrA genes per dry weight. The two marshes and their compartments were occupied by different methanogenic communities. In the C. lasiocarpa marsh, archaeal family Methanobacteriaceae, Rice Cluster II, and Methanosaetaceae co-dominated in the bulk soil, while Methanobacteriaceae was the exclusively dominant methanogen in the rhizosphere soil and roots. Families Methanosarcinaceae and Methanocellaceae dominated in the bulk soil of C. angustifolia marsh. Conversely, Methanosarcinaceae and Methanocellaceae together with Methanobacteriaceae dominated in the rhizosphere soil and roots, respectively, in the C. angustifolia marsh. Elevated atmospheric CO2 increased plant photosynthesis and belowground biomass of C. lasiocarpa and C. angustifolia marshes. However, it did not significantly change the abundance (based on mcrA qPCR), diversity, or community structure (based on high-throughput sequencing) of methanogens in any of the compartments, irrespective of plant type. Our findings suggest that the population and species of the dominant methanogens had weak responses to elevated atmospheric CO2. However, minor changes in specific methanogenic taxa occurred under elevated atmospheric CO2. Despite minor changes, methanogenic communities in different compartments of two contrasting freshwater marshes were rather stable under elevated atmospheric CO2.